2020
DOI: 10.15835/nbha48412151
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, anti-cancer and ameliorative activities of Spirulina platensis and pomegranate juice against hepatic damage induced by CCl4

Abstract: Due to the excessive impact of synthetic drugs, unravelling and employing safe, natural alternatives are now needed to resolve a number of diseases. In this research, we have evaluated hepatoprotective and antioxidant activities of Spirulina platensis and pomegranate juice in rats against hepatotoxicity induced by carbon tetrachloride (CCl4). Spirulina crude carotenoid extract was screened by UPLC-MS / MS. Activities of liver marker enzymes; measured aspartate aminotransferase (AST) and alanine aminotransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Singprecha et al [86] investigated the effect of ginger extract and ascorbic acid on antioxidant activity, implying that an antagonistic interaction between ascorbic acid and ginger, or herbal extracts, should be considered to avoid any potential health consequences. El-Beltagi et al [87], found that a mixture of Spirulina platensis and pomegranate juice ameliorate the rat hepatic harm caused by CCl 4 through its antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Singprecha et al [86] investigated the effect of ginger extract and ascorbic acid on antioxidant activity, implying that an antagonistic interaction between ascorbic acid and ginger, or herbal extracts, should be considered to avoid any potential health consequences. El-Beltagi et al [87], found that a mixture of Spirulina platensis and pomegranate juice ameliorate the rat hepatic harm caused by CCl 4 through its antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Batista et al [ 83 ] revealed that when estimating the amount of total phenols in biscuits enriched with spirulina algae, the addition of spirulina by 2% did not give any significant differences compared to the control sample, as the amount of phenols was 1.4 mg gallic acid/g, while the content of phenolics increased significantly to 1.6–1.7 mg gallic acid/g when spirulina was increased to 6%. El-Beltagi et al [ 8 ] studied that the aqueous extract of spirulina contained a significant amount of total flavonoids, which was 79.6 mg/g dry weight, and that the amount of total phenols was 16.0 mg/g dry weight. Consequently, these were used to enhance pomegranate juice because of the positive effects that these chemical compounds have on one’s health.…”
Section: Nutritional and Biochemical Components Of Spirulinamentioning
confidence: 99%
“…When compared to the rats who were fed the control diet, the rats that were given either pomegranate juice, spirulina extract, or both together had a considerable rise in their body weight. These liquids stimulated hunger, which ultimately resulted in weight gain [ 8 ]. In addition, Moradi et al [ 157 ] found that supplementation with spirulina significantly lowered body weight from −1.98 to −1.14 kg, notably in obese adults at a dosage of 4 g/day from −2.45 to −1.68 kg.…”
Section: Potential Health Benefits Of Spirulina From a Human Nutritio...mentioning
confidence: 99%
See 2 more Smart Citations